The Empirical Analysis of the Influence of Capital Structure on Corporate Value - You, Xiaoyi (2013)
With the expansion of the companies’ scale and the improvement of their decision-making level, companies not only concern the scale of financing, but also pay more attention to the ways of financing and the capital structure in order to enhance the company’s market value and achieve the best interest of investors. This thesis aims at figuring out whether there are relations between company’s capital structure and their enterprise value and if the relation exists, how the capital structure may influence the firm’s value and whether an optimal structure does exist for the companies to maximize their value.